Representasi Nilai-Nilai Karakter di Kampung Naga Sebagai Referensi Pengembangan Bahan Ajar Pendidikan Pancasila dan Kewarganegaraan - Suherman, Ade; Sekti, Pipyn Hidroga; Hidayat, Rahmat; Akbar, Gilang Muhamad; Yusup, Dani Mulyadi; Sutisna, Muhamad (CV. Kurnia Grup, 2024)
This study examines the representation of character values in Naga Village as a reference for the development of teaching materials for Pancasila and Citizenship Education (PPKn). Naga Village, as a traditional community in West Java, has local wisdom that is rich in cultural and moral values, such as environmental values, maintaining a clean and healthy lifestyle, fostering spirituality, applying discipline, and showing strong social concern. This study uses a qualitative approach with a case study method to explore how these values are integrated in the daily life of the people of Naga Village. Data was obtained through observation, in-depth interviews, and document analysis. The results of the study show that the character values in Naga Village are very relevant to the educational goals of PPKn, especially in the formation of attitudes and behaviors in accordance with Pancasila. Therefore, these values can be used as an important reference in the development of contextual and applicable teaching materials for students, in order to strengthen character and citizenship education in Indonesia.